Trade and Investment Linkages in Higher Education Services in Malaysia - Tham Siew Yean; Andrew Kam Jia Yi (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
This study aims to explore the trade and investment links in private higher education in Malaysia. Specifically, the study assesses whether, and if so, how trade and investment policies in general, and in the education sector in particular, are coordinated at the national level.
Keywords: F1; 330; Trade and Investment; Education Services; Mode 1; Malaysia